2017
DOI: 10.1177/2156869317718889
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Need for Mental Health Care: The Intersection of Race, Ethnicity, Gender, and Socioeconomic Status

Abstract: Racial/ethnic minority populations underutilize mental health services, even in the presence of psychiatric disorder, and differences in perceived need may contribute to these disparities. Using the Collaborative Psychiatric Epidemiology Surveys, we assessed how the intersections of race/ethnicity, gender, and socioeconomic status affect perceived need. We analyzed a nationally representative sample of U.S. adults (18 years or older; N=14,906), including non-Latino whites, Asian Americans, Latinos, African Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 89 publications
(151 reference statements)
2
55
0
Order By: Relevance
“…The majority of participants in this mental health pilot study were female, suggesting that they may be more likely than males to seek [20] and utilize mental health services [21,22]. White, non-Latino individuals represented the majority of patients in this study, which aligns with research reported by others regarding help-seeking behavior for mental health conditions [23]. This may speak to the reluctance of some groups of individuals (e.g., African Americans, non-white Hispanics) to seek mental healthcare services.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The majority of participants in this mental health pilot study were female, suggesting that they may be more likely than males to seek [20] and utilize mental health services [21,22]. White, non-Latino individuals represented the majority of patients in this study, which aligns with research reported by others regarding help-seeking behavior for mental health conditions [23]. This may speak to the reluctance of some groups of individuals (e.g., African Americans, non-white Hispanics) to seek mental healthcare services.…”
Section: Discussionsupporting
confidence: 74%
“…Other factors (e.g., mental health literacy, economic resouces) may partially explain some of these differences in Duke scores. For example, some non-white groups may experience disparities (e.g., limited access and ability to incorporate better food sources of essential amino acids), potentially affecting their response and ability to engage in more positive health behaviors [23].…”
Section: Discussionmentioning
confidence: 99%
“…showed that mental needs of women are more likely to be met than that of men. [ 29 ] Since the nature of emotional needs is related to social relationships, supports, and networks, it seems that in Iran, the wideness of familial networks and relationships, as a result of the increased quantity of relationships through more children and grandchildren, leads to a higher level of satisfaction in terms of emotional needs. Due to the special cultural characteristics dominant in Iran, men enjoy a wider and more comprehensive communicative range, and as compared to women, the intra- and inter-group relationships are more available for them, so it seems that their emotional needs are also met more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…This item was developed for the study to assess global subjective mental health as this perception signals need and action for help-seeking. Single-item assessments of perceived need are common in adult mental health literature (Fleishman & Zuvekas, 2007; Villatoro et al, 2018).…”
Section: Methodsmentioning
confidence: 99%